O-003 Temporal distribution of stroke volumes and clinical-diffusion mismatch in patients with proximal arterial occlusions. (4th July 2012) - Nogueira, R; Liebeskind, D; Souza, L; Hao, Q; Furie, K; Yoo, A; Saver, J; Lev, M; Gupta, R
Abstract : Background and Purpose: Previous studies have demonstrated that the benefit of reperfusion therapy declines over time. The Clinical-Diffusion Mismatch (CDM) model has been suggested as surrogate for salvable tissue in acute ischemic stroke (AIS) patients. We sought to describe the temporal behavior profile of infarct volumes and CDM in patients suffering AIS due to proximal arterial occlusion (PAO). Methods: We performed a retrospective analysis of consecutive AIS patients admitted to two large academic institutions fulfilling the following criteria: (1) Baseline NIHSS ≥8; (2) PAO defined as MCA-M1, intracranial ICA, or tandem cervical + ICA/MCA-M1 occlusion on admission CTA/MRA; and (3) MRI-DWI performed ≤8 h from time of stroke onset/last seen well (TSO). CDM was defined as baseline NIHSS ≥8 and DWI volume ≤25cc (as proposed by Davalos et al ). Linear regression analysis was performed to define the changes on DWI lesion volume on presentation over time. The observed TSO to MRI were broken down into quartiles to look for any differences in the distribution of the baseline variables over time. Results: A total of 132 consecutive patients were identified (mean age, 66±16.8 years; 57% females; mean baseline NIHSS 17.5±5.3; occlusion site: MCA-M1, 64%; intracranial-ICA, 29%; tandem, 5%, mean TSO to DWI, 269.5±105.48 min). The mean DWI stroke volume on presentation was 46.7±54.8 cc (range, 0.19–436.1) and 63 (46.7%) patients had CDM. There was no significant changes in age, gender, baseline NIHSS, or occlusion site among the different time quartiles. Median infarct volume (cc) increased (quartile #1=8.5; #2=30.1; #3=38.5; #4=29.4) and the chances of having a CDM decreased (p<0.0001) across the different time quartiles. However, there was an overall poor correlation between DWI lesion volume on presentation and TSO to MRI (R 2 =0.031, Abstract O-003 figure 1 ) and a significant proportion of the patients still had a CDM at later time epochs (#1=91.1% (20/22); #2=47.8% (11/23); #3=34.4% (21/61); #4=42.3% (11/26)). Conclusions: Although infarct volume increases and the amount of penumbral tissue decreases over time, many patients with PAO will still have salvable penumbra at the later time epochs. This reflects individual differences in anatomic and physiological characteristics including the strength of collateral flow and highlights that selected patients may benefit from reperfusion therapy even at the later time windows. Competing interests: R Nogueira: Concentric Medical; ev3 Neurovascular; Coaxia. D Liebeskind: Concentric Medical; Neurovascular; Coaxia. L Souza: None. Q Hao: None. K Furie: NIH. A Yoo: Penumbra. J Saver: ev3 Neurovascular; NIH. M Lev: Coaxia. R Gupta: Concentric Medical; Codman; Coaxia.